2014
DOI: 10.4315/0362-028x.jfp-13-353
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of Listeria innocua to Polystyrene: Effects of Ionic Strength and Conditioning Films from Culture Media and Milk Proteins

Abstract: It is recognized that bacterial adhesion usually occurs on conditioning films made of organic macromolecules absorbed to abiotic surfaces. The objectives of this study were to determine the extent to which milk protein-coated polystyrene (PS) pegs interfere with biofilm formation and the synergistic effect of this conditioning and hypertonic growth media on the bacterial adhesion and biofilm formation of Listeria innocua, used as a nonpathogenic surrogate for Listeria monocytogenes. PS pegs were uncoated (bare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This conditioning layer also enhanced the anti-corrosion performance of the coatings (He et al, 2015). Additionally, other authors have shown that protein films reduced the bacterial adhesion to different surfaces (Chapman et al, 2001;Dat et al, 2014;Merghni et al, 2016;Robitaille et al, 2014).…”
Section: Introductionmentioning
confidence: 82%
“…This conditioning layer also enhanced the anti-corrosion performance of the coatings (He et al, 2015). Additionally, other authors have shown that protein films reduced the bacterial adhesion to different surfaces (Chapman et al, 2001;Dat et al, 2014;Merghni et al, 2016;Robitaille et al, 2014).…”
Section: Introductionmentioning
confidence: 82%
“…Although one might think that adsorbed cell components and related molecules can automatically enhance cell retention and reduce surface hygiene, it is known from several studies that proteins such as bovine serum albumin (BSA), gelatin, fibrinogen and pepsin adsorbed to surfaces may inhibit bacterial attachment [11],[12],[13]. Recently, it has been shown that surface preconditioning has potential to prevent bacterial adhesion to processing surfaces [14][18]. In order to elucidate about the process of bacterial contamination in dairy industry, Dat et al [16] investigated the influence of surface conditioning with dairy by-products such as skimmed milk, buttermilk and butter serum (which possess different compositions) on the bacterial attachment behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In 1993, Helke et al (18) concluded that casein, a-lactalbumin, and b-lactoglobulin inhibited the attachment of Listeria monocytogenes and Salmonella enterica serovar Typhimurium to stainless steel and Buna-N surfaces when present in the attachment menstruum or when the surfaces were pretreated with these proteins. Conditioning films made of whey protein isolate (WPI), b-lactoglobulin, and bovine serum albumin (BSA) have been shown to have a transient effect by slowing down the adhesion of Listeria innocua to polystyrene surfaces (19). Individual milk proteins a-casein, b-casein, κ-casein, and a-lactalbumin have been known to reduce the attachment of Staphylococcus aureus and L. monocytogenes to stainless steel surfaces (20).…”
Section: Resultsmentioning
confidence: 99%